Analisis Teks Pancasila dalam Perspektif Dimensi Dakwah Kebangsaan - sarkawi, Sarkawi; Arifin, Zainal; Zulham, Zulham; Daulay, Mahmud Yunus; Rakatiwi, Yolanda; Hermanto, Budi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2024)
Indonesia is a unitary state that adheres to the state ideology with an open system, a pluralistic and multicultural society, and various races, tribes, ethnicities and religions. The Indonesian state recognizes at least six religions. Lately, opinions have often emerged that mention the separation of religion from Pancasila; this is interesting to do further study. Does Pancasila conflict with religion? This research was conducted through a literature study that analyzed the Pancasila text from the perspective of preaching. Through a historical approach and content analysis, literature and references related to the objectives and focus of the research are searched for and collected. Data sources were obtained through books, journals, and observations in documentary films. Based on the discussion conducted, it can at least be concluded that the Pancasila text formulated by national figures, including Ulama, that the five principles in Pancasila contain exceptional preaching values and fundamental and principled meanings in Islamic teachings, both divinity, humanity, unity, democracy and wisdom, and justice are essential things to do and are teachings in Islam.